2021
DOI: 10.1021/acs.est.1c00248
|View full text |Cite
|
Sign up to set email alerts
|

Has Carbon Emissions Trading Reduced PM2.5 in China?

Abstract: China today has an urgent need to develop low-carbon policies that also address local air pollution. This study uses a difference-in-differences model to estimate the extent to which China’s Emissions Trading Scheme (ETS), which directly addresses CO2 emissions, has also generated cobenefits by reducing PM2.5. Using monthly PM2.5 concentration and weather data for 297 Chinese cities from January 2005 to December 2017, we find that (1) China’s ETS has reduced PM2.5 concentrations by 4.8%, and this reduction eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(50 citation statements)
references
References 55 publications
0
50
0
Order By: Relevance
“…Since the ETS is a market-based mechanism for emission reduction, the reduction effects are bound to vary with the performances of pilot markets [See (33) for a recent review].…”
Section: Further Checks On Pilot Market Performances and Post-pandemi...mentioning
confidence: 99%
“…Since the ETS is a market-based mechanism for emission reduction, the reduction effects are bound to vary with the performances of pilot markets [See (33) for a recent review].…”
Section: Further Checks On Pilot Market Performances and Post-pandemi...mentioning
confidence: 99%
“…Most studies concluded that the ETS is an effective policy tool in carbon emissions reduction at provincial, municipal, and corporate levels (Gao et al, 2020;Shen et al, 2020;, The emission reduction effect increases annually with the implementation of the policy (Zhang and Zhang, 2019). Some researchers suggest that such action also reduces other pollutants such as PM2.5 and SO 2 , promoting China's low-carbon innovation and economic development and finally bringing in more environmental dividends (Feng et al, 2021b;Liu et al, 2021). Wang et al (2020) adopted the difference-in-differences (DID) model to demonstrate a positive correlation between the ETS and low-carbon economic transformation; however, researchers also argued that the ETS may improve the efficiency of emission reduction, but the actual effect remains relatively weak (Zhu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the impact mechanism of the European Union Emissions Trading System (EU ETS) have argued that the EU ETS reduces carbon emissions mainly through technological innovation (Jaraitė and Di Maria, 2012;Calel and Dechezleprêtre, 2016). In a similar scenario, certain Chinese scholars have argued that China's ETS reduces carbon emissions by reducing energy consumption and optimizing energy structure, while the emission reduction effect of technological innovation is not significant (Xuan et al, 2020;Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolution of air pollution can be explored based on big data from different time dimensions, such as hourly, weekly, quarterly, and annual perspectives [15]. Some researchers have discussed the impact mechanisms of the COVID-19 pandemic [16], urbanization [17], foreign direct investment [18], climate change [19], carbon emissions trading [20], meteorological conditions [21], and tourism development [22] on air pollution. The results of this research have shown a negative inhibition, positive promotion, or nonlinear effects.…”
Section: Introductionmentioning
confidence: 99%